The effects of dolomitization on petrophysical properties and fracture distribution within rift-related carbonates (Hammam Faraun Fault Block, Suez Rift, Egypt). (March 2018) - Korneva, I.; Bastesen, E.; Corlett, H.; Eker, A.; Hirani, J.; Hollis, C.; Gawthorpe, R.L.; Rotevatn, A.; Taylor, R.
Abstract: Petrographic and petrophysical data from different limestone lithofacies (skeletal packstones, matrix-supported conglomerates and foraminiferal grainstones) and their dolomitized equivalents within a slope carbonate succession (Eocene Thebes Formation) of Hammam Faraun Fault Block (Suez Rift, Egypt) have been analyzed in order to link fracture distribution with mechanical and textural properties of these rocks. Two phases of dolomitization resulted in facies-selective stratabound dolostones extending up to two and a half kilometers from the Hammam Faraun Fault, and massive dolostones in the vicinity of the fault (100 metres). Stratabound dolostones are characterized by up to 8 times lower porosity and 6 times higher frequency of fractures compared to the host limestones. Precursor lithofacies type has no significant effect on fracture frequency in the stratabound dolostones. At a distance of 100 metres from the fault, massive dolostones are present which have 0.5 times porosity of precursor limestones, and lithofacies type exerts a stronger control on fracture frequency than the presence of dolomitization (undolomitized vs. dolomitized). Massive dolomitization corresponds to increased fracture intensity in conglomerates and grainstones but decreased fracture intensity in packstones. This corresponds to a decrease of grain/crystal size in conglomerates and grainstones and its increase in packstones after massive dolomitization. Since fractures may contribute significantly to the flow properties of a carbonate rock, the work presented herein has significant applicability to hydrocarbon exploration and production from limestone and dolostone reservoirs, particularly where matrix porosities are low.